Coated cutting tool with preferred orientation

CN118207513BActive Publication Date: 2026-10-27ZHUZHOU CEMENTED CARBIDE CUTTING TOOLS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202211625481.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-16
Publication Date
2026-10-27
Estimated Expiration
2042-12-16

AI Technical Summary

Technical Problem

但由于PVD TiAlN中Al含量限制,其对性能影响仍有限

Benefits of technology

[0033]1.本发明针对AlTiN涂层中Al含量限制问题,实现了在切削刀具表面沉积含O的高Al含量的立方晶体结构且具有优选的结晶生长取向的AlxTi1-xN1-y-zCyOz涂层。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118207513B_ABST
    Figure CN118207513B_ABST
Patent Text Reader

Abstract

This invention discloses a coated cutting tool with a preferred orientation, comprising a tool substrate and a wear-resistant coating disposed on the tool substrate, wherein the wear-resistant coating comprises at least one layer of Al. x Ti 1‑x N 1‑y‑z C y O z The coating, 0.65≤x≤0.98, 0<y<0.2, 0<z<0.18, the Al x Ti 1‑x N 1‑y‑z C y O z The coating has a preferred texture orientation relative to the {200} plane of the crystal, the Al x Ti 1‑x N 1‑y‑z C y O z The texture factor TC(200) of the coating is ≥1.5. The coated cutting tools of this invention have excellent wear resistance and anti-adhesion properties, and are suitable for efficient machining of difficult-to-machine materials such as cast iron, stainless steel and high-temperature alloys.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of coated cutting tool technology, and relates to a coated cutting tool with preferred orientation, specifically a coated cutting tool with excellent wear resistance and anti-adhesion properties. Background Technology

[0002] TiAlN coatings possess excellent properties such as high hardness, high oxidation temperature, good hot hardness, strong adhesion, low coefficient of friction, and low thermal conductivity. Studies show that Ti... 1-x Al x The structure and properties of nitrogen-containing coatings largely depend on the Al content. With increasing Al content, the coating grains become finer, and both hardness and oxidation resistance improve to some extent. However, beyond a certain critical value, the appearance of hexagonal close-packed AlN (h-AlN) causes a sharp decline in its mechanical properties. For PVD-Ti... 1-x Al x Nitrogen coatings, with a critical Al content of approximately 0.5-0.67 at.%, are widely used in high-performance machining of difficult-to-machine materials. Meanwhile, single-phase cubic Ti with an Al content as high as 0.9% can be prepared using CVD methods. 1-x Al x N-coatings, for example, patent document WO2007003648A discloses a method for preparing single-phase Ti with a cubic NaCl structure by CVD. 1-x Al x The N-coating and its preparation method, with a stoichiometric coefficient of 0.75. <x≤0.93。

[0003] To further improve Ti 1-x Al x N coating performance, in Ti 1-x Al xIntroducing other elements into the N coating. CVD-AlTiCN is a typical composition-modified coating with high hardness, high oxidation temperature, good thermal hardness, strong adhesion, low friction coefficient, and low thermal conductivity. Compared with CVD AlTiN coating, the structure and properties of the AlTiCN coating are greatly changed due to the introduction of C element. However, in existing related studies, the prepared CVD-AlTiCN coating has grain coarsening and poor surface smoothness, which has an adverse effect on performance. The literature (Jie Zhang, et al. Impact of oxygen content on the thermal stability of Ti-Al-ON coatings based on computational and experimental studies[J]. Acta Materialia 227(2022)117706) reported the introduction of O element into PVD TiAlN by cathodic arc ion plating technology to prepare PVD TiAlNO coating, which has better performance than conventional PVD TiAlN coating. However, due to the limitation of Al content in PVD TiAlN, its impact on performance is still limited.

[0004] It has been found that coatings with specific preferred grain orientations exhibit different properties in PVD and CVD coatings, and demonstrate superior performance for different processing conditions. WO2016148056A discloses a CVD-Ti 1- x Al x C y N 1-y The coating and its preparation method, and limited to the upper layer fcc-Ti 1-x Al x C y N 1-y Middle layer: I(200) / I(111)>10; Lower layer: fcc-Ti 1-x Al x C y N 1-y In the case of I(200) / I(111) < 3, to further improve the performance of the coating, Japanese Patent JP2019084671A discloses a CVD AlTiCNO coating. However, the improvement of the role of oxygen in the coating is achieved by continuously increasing the amount of oxygen applied along the thickness direction in the coating normal direction. However, with further research, different methods can be adopted to further improve the coating performance of oxygen-containing CVD AlTiCNO coating materials. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a coated cutting tool with preferential orientation that has excellent wear resistance, anti-adhesion properties and cutting performance.

[0006] To solve the above-mentioned technical problems, the present invention proposes the following technical solution.

[0007] A coated cutting tool with preferred orientation includes a tool substrate and a wear-resistant coating disposed on the tool substrate, the wear-resistant coating comprising at least one layer of Al. x Ti 1-x N 1-y-z C y O z The coating, 0.65≤x≤0.98, 0<y<0.2, 0<z<0.18, the Al x Ti 1-x N 1-y-z C y O z The coating has a preferred texture orientation relative to the {200} plane of the crystal, the Al x Ti 1-x N 1-y-z C y O z The texture factor TC(200) of the coating is ≥1.5.

[0008] TC(hkl) is defined as follows:

[0009]

[0010] in,

[0011] I(hkl) = (hkl) the measured intensity of the reflected light;

[0012] I0(hkl) = Standard intensity of reflection of (200) based on the standard powder diffraction data of the applied JCPDF card No. 00-46-1200;

[0013] I(hkl) i =(hkl) i The intensity of the reflected light;

[0014] I0(hkl) i =Based on the standard powder diffraction data (hkl) of the applied JCPDF card No. 00-46-1200 i Standard intensity of reflection;

[0015] n = the number of reflections used in the calculation, here: n = 6;

[0016] (hkl) i The (hkl) usedi The reflective crystal planes are: (111), (200), (220), (311), (331), and (420).

[0017] Preferably, in the above-mentioned coated cutting tool with preferred orientation, the full width at half maximum (FWHM) of the X-ray diffraction peak of the {200} plane of the crystal is <0.8°.

[0018] More preferably, in the above-mentioned coated cutting tool with preferred orientation, the full width at half maximum (FWHM) of the X-ray diffraction peak of the {200} plane of the crystal is less than 0.5°.

[0019] The aforementioned coated cutting tools with preferred orientation, preferably, the Al x Ti 1-x N 1-y-z C y O z The coating is a periodic coating consisting of alternating Al-rich layers with high Al content and Ti-rich layers with high Ti content, wherein both the Al-rich layers and the Ti-rich layers are nanolayered structures.

[0020] The aforementioned coated cutting tool with preferred orientation, preferably, is positioned along the Al... x Ti 1-x N 1-y-z C y O z Along the growth direction of the coating, the region on the Al element distribution curve that is higher than the average atomic fraction of Al in the coating represents the period width d of the Al-rich layer. Al The region on the Al element distribution curve that is lower than the average atomic fraction of Al in the coating represents the period width d of the Ti-rich layer. Ti , satisfying d Al ≤150nm, d Ti ≤120nm, more preferably, d Al ≤100nm, d Ti ≤90nm, further preferred, d Al ≤50nm, d Ti ≤45nm.

[0021] The aforementioned coated cutting tool with preferred orientation, along the Al x Ti 1-x N 1-y-z C y O z In the growth direction of the coating, the sum of the widths of each period of the Al-rich layer is d Al-total With the Al x Ti 1-x N 1-y-z C y O zThe total thickness h of the coating (4) satisfies 0.5 < d Al-total / h<1.

[0022] The aforementioned coated cutting tools with preferred orientation, preferably, the Al x Ti 1-x N 1-y-z C y O z The concentration of oxygen in the coating varies periodically along the Al... x Ti 1-x N 1-y-z C y O z In the growth direction of the coating, Al x Ti 1-x N 1-y-z C y O z The width between two adjacent peaks on the O element distribution curve in the coating is set as the period width d of the periodic concentration change of O element. O d O ≤200nm.

[0023] The aforementioned coated cutting tools with preferred orientation, preferably, the Al x Ti 1-x N 1-y-z C y O z The surface roughness Ra of the coating is ≤0.25μm.

[0024] The aforementioned coated cutting tools with preferred orientation, preferably, the Al x Ti 1-x N 1-y-z C y O z The coating has at least 85% by volume a face-centered cubic crystal structure, more preferably, the Al x Ti 1-x N 1-y-z C y O z The coating has at least 89% by volume a face-centered cubic crystal structure, and more preferably, the Al x Ti 1-x N 1-y-z C y O z The coating has a face-centered cubic crystal structure of at least 93% by volume.

[0025] The aforementioned coated cutting tools with preferred orientation, preferably, are Al... x Ti 1-x N 1-y-z C y Oz The coating has a nanohardness of ≥30 GPa.

[0026] Preferably, in the aforementioned coated cutting tools with preferred orientation, the wear-resistant coating further includes a layer disposed between the tool substrate and the Al. x Ti 1-x N 1-y-z C y O z A hard substrate layer between the coating layers, wherein the thickness of the hard substrate layer is 0.1 μm to 8 μm, preferably 0.3 μm to 5 μm, more preferably 0.5 μm to 3 μm, and the hard substrate layer includes one or a combination of CVD deposited TiN layer, TiCN layer and h-AlN layer.

[0027] Preferably, in the aforementioned coated cutting tools with preferred orientation, the wear-resistant coating further includes a layer disposed on the Al. x Ti 1-x N 1-y-z C y O z A hard surface layer above the coating, the thickness of the hard surface layer being >0.1 μm, the hard surface layer comprising one or a combination of CVD-deposited TiN layers, TiC layers, TiCN layers and h-AlN layers.

[0028] Preferably, in the above-mentioned coated cutting tools with preferred orientation, the wear-resistant coating has a total thickness of 2μm to 25μm.

[0029] Surprisingly, in a further preferred embodiment of the invention, Al x Ti 1-x N 1-y-z C y O z The coating has an extremely smooth surface with a surface roughness Ra < 0.25 μm. The smooth coated tool surface results in superior tool surface quality and machining performance.

[0030] Surprisingly, in a further preferred embodiment of the invention, Al x Ti 1-x N 1-y-z C y O z The coating exhibits a nanohardness (HV) of ≥30 GPa. Coatings with excessively low hardness exhibit low wear resistance; the method of this invention achieves the Al of this invention. x Ti 1-x N 1-y-z C y O z High hardness of the coating.

[0031] In this invention, the tool substrate includes a tool substrate made of superhard materials such as cemented carbide, cermet, ceramic, steel, or cubic boron nitride.

[0032] Compared with the prior art, the advantages of the present invention are as follows:

[0033] 1. This invention addresses the limitation of Al content in AlTiN coatings by achieving the deposition of a cubic crystal structure with high Al content and preferred crystal growth orientation on the surface of cutting tools. x Ti 1-x N 1-y-z C y O z coating.

[0034] 2. The Al of the present invention x Ti 1-x N 1-y-z C y O z By controlling the texture orientation and the interlayer microstructure of the Ti-rich / Al-rich layers, the coating achieves a nanohardness of over 30GP, significantly improving its wear resistance.

[0035] 3. The Al of the present invention having an ultrafine nanocrystalline structure x Ti 1-x N 1-y-z C y O z The coating has an extremely smooth surface with a very low surface roughness Ra value, resulting in excellent cutting performance.

[0036] 4. The coated cutting tool of the present invention has excellent wear resistance and anti-adhesion properties, and is suitable for efficient machining of difficult-to-machine materials such as cast iron, stainless steel and high-temperature alloys. Attached Figure Description

[0037] Figure 1 This is a schematic diagram of the tool A2 in Embodiment 1 of the present invention.

[0038] Figure 2 Al in the cutting tool A1 of Embodiment 1 of the present invention x Ti 1-x N 1-y-z C y O z TEM morphology image of the coating (STEM-HAADF-BF).

[0039] Figure 3 Al in the cutting tool A1 of Embodiment 1 of the present invention x Ti 1-x N 1-y-z C y O zEnergy dispersive spectral analysis of the nanolayered structure region in the coating.

[0040] Legend:

[0041] 1. Tool body; 2. Wear-resistant coating; 3. Hard base layer; 4. Al x Ti 1-x N 1-y-z C y O z 5. Coating; Hard surface layer. Detailed Implementation

[0042] The present invention will be further described below with reference to the accompanying drawings and specific preferred embodiments, but this does not limit the scope of protection of the present invention. All materials and instruments used in the following embodiments are commercially available.

[0043] Example 1

[0044] A coated cutting tool with preferred orientation according to the present invention, such as Figure 1 As shown, the tool includes a tool substrate 1 and a wear-resistant coating 2 disposed on the tool substrate 1. The wear-resistant coating 2 includes at least one layer of Al prepared by chemical vapor deposition (CVD). x Ti 1-x N 1-y-z C y O z Coating 4, where 0.65 ≤ x ≤ 0.98, 0 < y < 0.2, 0 < z < 0.18; measurements were performed using Cuka radiation, Al x Ti 1-x N 1-y-z C y O z Coating 4 exhibits an X-ray diffraction pattern and a preferred crystal growth orientation, Al x Ti 1- x N 1-y-z C y O z Coating 4 has a preferred texture orientation relative to the {200} plane of the crystal, Al x Ti 1-x N 1-y-z C y O z The texture factor TC(200) of the coating is ≥1.5.

[0045] In this embodiment, Al x Ti 1-x N 1-y-z C y O z The full width at half maximum (FWHM) of the X-ray diffraction peak in the {200} plane of coating 4 is <0.8°.

[0046] In this embodiment, Al x Ti 1-x N 1-y-z C y O z Coating 4 has a face-centered cubic crystal structure of over 92%.

[0047] In this embodiment, Al x Ti 1-x N 1-y-z C y O z Coating 4 is a multi-period coating composed of alternating Al-rich layers with high Al content and Ti-rich layers with high Ti content. Both the Al-rich layers and the Ti-rich layers have nano-layered structures.

[0048] In this embodiment, Al x Ti 1-x N 1-y-z C y O z Any cross section within coating 4 perpendicular to the surface of the tool substrate 1, along Al x Ti 1-x N 1-y-z C y O z Along the growth direction of coating 4, the region on the Al element distribution curve that is higher than the average atomic fraction of Al in the coating is the period width d of the Al-rich layer. Al The region on the Al element distribution curve that is lower than the average atomic fraction of Al in the coating represents the period width d of the Ti-rich layer. Ti , satisfying d Al ≤150nm, d Ti ≤120nm, preferably d Al ≤100nm, d Ti ≤90nm, more preferably d Al ≤50nm, d Ti ≤45nm.

[0049] In this embodiment, Al x Ti 1-x N 1-y-z C y O z Any cross-section within coating 4 perpendicular to the tool substrate surface, along Al x Ti 1-x N 1-y-z C y O z In the growth direction of coating 4, the sum of the widths of each period of the Al-rich layer is d Al-total With Al x Ti 1-x N 1-y-z Cy O z The total thickness h of coating 4 satisfies 0.5 < d. Al-total / h<1.

[0050] In this embodiment, Al x Ti 1-x N 1-y-z C y O z The concentration of O in coating 4 exhibits periodic changes, while Al... x Ti 1-x N 1-y- z C y O z Any cross section within coating 4 perpendicular to the surface of the tool substrate 1, along Al x Ti 1-x N 1-y-z C y O z In the growth direction of coating 4, Al x Ti 1-x N 1-y-z C y O z The width between two adjacent peaks on the atomic fraction distribution curve of O element in coating 4 is defined as the period width d. O d O ≤200nm.

[0051] In this embodiment, Al x Ti 1-x N 1-y-z C y O z The surface roughness Ra of coating 4 is ≤0.25μm.

[0052] In this embodiment, Al x Ti 1-x N 1-y-z C y O z The nano-hardness of coating 4 is ≥30GPa.

[0053] In this embodiment, the wear-resistant coating 2 further includes a layer disposed on Al. x Ti 1-x N 1-y-z C y O z The hard substrate layer 3 between the coating 4 and the tool substrate 1 has a thickness of 0.1 μm to 8 μm and includes at least one layer selected from CVD deposited TiN, TiCN, TiC, and h-AlN layers. In this embodiment, a TiN layer is specifically used as the hard substrate layer 3.

[0054] In this embodiment, the wear-resistant coating 2 further includes a layer disposed on Al. x Ti 1-x N 1-y-z C y O z A hard surface layer 5 is applied above coating 4. The thickness of the hard surface layer 5 is >0.1 μm. The hard surface layer 5 includes one or a combination of CVD-deposited TiN, TiC, TiCN, and h-AlN layers. In this embodiment, the tool A2 uses a hard surface layer TiN coating.

[0055] In this embodiment, the wear-resistant coating 2 has a total thickness of 2μm to 25μm.

[0056] In this embodiment, the tool substrate 1 is a cemented carbide substrate, but it is not limited to this. It can also be a substrate made of superhard materials such as cermet, ceramic, steel or cubic boron nitride.

[0057] The method for preparing the coated cutting tool with preferred orientation in this embodiment includes the following steps:

[0058] (1) A mixture of powders with a mass fraction of 9.5% Co, 1.5% TaNbC, 0.4% Cr3C2 and the remainder being WC with a particle size of 1.6-1.9 μm is pressed, sintered and ground to produce a WC-Co cemented carbide matrix with the blade shape specified by ISO standard SNGX1205ANN-GM.

[0059] (2) Prepare indexable coated cutting inserts and perform coating in a CVD coating furnace equipped with a low-pressure system (LPS), such as a Bernex BPX530L CVD coating equipment. A hard base layer TiN is deposited on the tool substrate 1 using existing CVD processes, with a deposition thickness of 0.3-2.0 μm, and the thickness is highly positively correlated with the deposition time.

[0060] (3) Deposition of Al x Ti 1-x N 1-y-z C y O z Coating 4: Continue depositing Al on the hard TiN substrate layer. x Ti 1-x N 1-y-z C y O z Coating 4 employs a low-pressure CVD process, with reaction gases introduced into the coating furnace via two gas pipelines. After preheating and mixing, the two gases, V1 and V2, undergo Al deposition in the CVD reactor. x Ti 1-x N 1-y-z C y Oz The deposition parameters for coating 4 are shown in Table 1. The deposition times for tools A1 and A2 were 80 min and 150 min, respectively. The preheater and graphite rod rotation speed for tool A1 was 0.5 rpm, and the preheater and graphite rod rotation speed for tool A2 was 3 rpm. x Ti 1-x N 1-y-z C y O z The thickness of coating 4 is highly positively correlated with deposition time.

[0061] (4) Deposition of hard surface layer 5: For tool A2 in Al x Ti 1-x N 1-y-z C y O z The surface of coating 4 was further coated with a hard TiN coating in a CVD coating furnace equipped with a low-pressure system (LPS). The reaction gas was introduced into the coating furnace through two gas lines (V1 and V2). In the V1 gas, the volume fraction of TiCl4 was 1.84%, the volume fraction of Ar was 6%, and the volume fraction of H2 was 92.16%. In the V2 gas, the volume fraction of NH3 was 11.25% and the volume fraction of H2 was 88.75%. The volume ratio of the two gases, T1 / T2, was 5:1. The rotation speed of the preheater and graphite rod was 0.5 rpm. The deposition temperature was 800℃, the deposition pressure was 12 mbar, and the deposition time was 30 min.

[0062] Table 1A1 x Ti 1-x N 1-y-z C y O z Coating deposition process parameters

[0063]

[0064] Coating thickness inspection:

[0065] A vertical section containing the coating was obtained by cutting along the vertical direction of the blade with a diamond saw blade. After mounting, grinding and polishing, the thickness of each layer of the coating was determined by metallographic microscope, as shown in Table 2.

[0066] Table 2 Coating thickness in Example 1

[0067]

[0068] The Al of the present invention x Ti 1-x N 1-y-z C y O zThe thickness of coating 4 has a certain positive correlation with the deposition time, and the coating thickness can be adjusted by the deposition time.

[0069] Coating chemical composition analysis:

[0070] A vertical cross-section containing the coating was obtained by cutting along the vertical direction of the blade using a diamond saw blade. After mounting, grinding, and polishing, the coating composition was analyzed by scanning electron microscopy (STEM-EDS), and the results are shown in Table 3. The Al of this invention... x Ti 1-x N 1-y- z C y O z The coating composition has a high Al content with a stoichiometric coefficient x value of 0.65 to 0.98, a C content stoichiometric coefficient y value of 0 < y < 0.2, and an O content stoichiometric coefficient z value of 0.0001 to 0.18.

[0071] Table 3. Al in Example 1 x Ti 1-x N 1-y-z C y O z Coating composition (at%)

[0072] A1 10.91 38.29 5.45 39.3 6.05 0.78 0.11 0.12 A2 5.46 44.24 5.58 40.07 4.65 0.89 0.08 0.09

[0073] Coating crystallization preferred orientation detection and full width at half maximum (FWHM) of the {200} plane:

[0074] X-ray diffraction (XRD) was used to determine the preferred crystal orientation and the full width at half maximum (FWHM) of the {200} plane. Table 4 shows the results of the texture orientation detection and the FWHM of the {200} plane of the prepared coated blades.

[0075] Table 4 Al x Ti 1-x N 1-y-z C y O z Coating orientation

[0076]

[0077] Coating microstructure and morphology inspection:

[0078] Figure 2 Al in the cutting tool A1 of this invention x Ti 1-x N 1-y-z C y O z The TEM morphology (STEM-HAADF-BF) of coating 4, in bright-field imaging mode, shows bright and dark fringes in the Ti-rich and Al-rich layers. (This is in contrast to the previous sentence, which seems unrelated and possibly a fragment from another context.) Figure 2 Energy dispersive spectroscopy (EDS) analysis data of the layered morphology of the region was used to plot the elemental content (intensity) distribution of the EDS line scans, such as... Figure 3 As shown. According to Figure 3 It can be seen that along Al x Ti 1- x N 1-y-z C y O z In the growth direction of coating 4, it consists of alternating Ti-rich and Al-rich layers, with periodic concentration variations of Ti and Al. According to... Figure 3 Al-rich layer width period d Al The width and periodicity of the Ti-rich layer are approximately 15 nm and 5.5 nm. Ti The wavelengths are approximately 7.5nm and 3nm. According to... Figure 2 and Figure 3 The ratio of the width period of the Al-rich layer to the total thickness can be calculated from the width periods of the Al-rich and Ti-rich layers. According to... Figure 3 The ratio of the periodicity of the Al-rich layer width to the total thickness is 0.66. Simultaneously, the O element also exhibits periodic concentration variations. According to... Figure 3 In any cross section perpendicular to the surface of the tool base 1, along Al x Ti 1-x N 1-y-z C y O z In the growth direction of coating 4, Al x Ti 1-x N 1-y-z C y O z The width d between two adjacent peaks on the atomic fraction distribution curve of O element in coating 4 O The wavelengths were successively 14nm, 6nm, 4nm, 6nm, 12nm, 10nm, 8nm, 14nm, 6nm, and 4nm, with a maximum of 14nm. Using the same analytical and detection method, the Al content of tool A2 was measured. x Ti 1-x N 1-y-z C y O z The Al-rich layer in the coating has a width period d Al The width and periodicity of the Ti-rich layer are approximately 12nm and 4nm. Ti The thicknesses are approximately 5 nm and 2 nm. The ratio of the periodic width of the Al-rich layer to the total thickness is 0.70. The periodic width d of the O element periodic concentration variation is... OThe maximum size is approximately 12 nm. EDS analysis showed that the narrow region exhibiting dark lamellae in BF and bright lamellae in HAADF had a higher Ti proportion and a lower Al proportion compared to the wider region. However, the nitrogen proportion was of the same order of magnitude across all regions at the measurement precision. All components determined by EDS were identical to those determined by XRD.

[0079] Coating nano-hardness testing:

[0080] The coated blades were polished and then subjected to nano-hardness testing, as shown in Table 5.

[0081] Table 5. Al of Example 1 x Ti 1-x N 1-y-z C y O z Layer nano-hardness test results

[0082] Hv / GPa 31.2±1.0 30.7±0.9

[0083] Coating surface roughness inspection:

[0084] Al was measured using a surface roughness meter. x Ti 1-x N 1-y-z C y O z The surface roughness Ra of the coating was measured, and the results are shown in Table 6. The Al of this invention... x Ti 1-x N 1-y-z C y O z The coating has an extremely smooth surface with a surface roughness Ra value of less than 0.12 μm.

[0085] Table 6. Al of Example 1 x Ti 1-x N 1-y-z C y O z Coating surface roughness test results

[0086] Ra(μm) 0.12 0.11

[0087] Performance comparison test

[0088] Cutting performance comparison tests were conducted on the cutting tools A1 and A2 of the present invention, produced according to Example 1, and the comparative coated tools P1 and C2 of Example 1, which have the same tool substrate. The comparative coated tool is tool P1 coated using a conventional PVD process: Ti 0.50 Al 0.50N (total thickness 4.0 μm) and C2 tool: TiN / MT-TiCN / Al2O3 / TiN (layer thicknesses of each layer are 0.8 μm, 5 μm, 4 μm and 0.7 μm respectively, total thickness 10.5 μm).

[0089] The cutting tools described above were subjected to milling tests as shown in Table 7.

[0090] Table 7 Milling Test Conditions

[0091]

[0092] Table 8 Comparison of Experimental Results

[0093] A1 (This invention) 45 0.31 A2 (This invention) 56 0.30 P1 (Comparison Knife) 26 0.32 C2 (Comparison Tool) 30 0.31

[0094] According to Table 8, the life of the coated tool of the present invention is significantly better than that of the comparative tool, demonstrating excellent wear resistance.

[0095] Example 2: Cutting Test

[0096] A WC-Co cemented carbide matrix with a cutting tool shape specified by ISO standard RPMT1204MO was manufactured by pressing, sintering, and grinding a mixture powder containing 10% Co, 0.64% Cr3C2, and the balance WC with a particle size of 0.6-0.8 μm. Tools A3 and A4 were prepared using the same process as tools A1 and A2 in Example 1, and their cutting performance was compared with that of a control tool P2 with the same substrate. The control tool P2 was coated using a conventional PVD process: Ti 0.42 Al 0.58 N, total thickness 3.8μm.

[0097] The T3, T4, and P2 cutting tools were subjected to turning tests as shown in Table 9. The test equipment was a PG2517 gantry milling machine, and the test tool holder was FWR06-032-XP32-RP12-03C(30 / 180), using single-tooth cutting.

[0098] Table 9 Milling Test Conditions

[0099]

[0100] After machining one surface, the tool wear and workpiece surface roughness are shown in Table 10.

[0101] Table 10 Comparison of Experimental Results

[0102] A3 (This invention) 0.16 0.62 A4 (This invention) 0.21 0.79 P2 (Comparison Tool) 0.32 1.45

[0103] According to Table 10, under the same processing time, the wear of the coated tool of the present invention and the surface roughness of the processed workpiece are significantly lower than those of the comparative tool, which shows that the tool of the present invention has excellent wear resistance and anti-adhesion properties.

[0104] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make many possible variations and modifications to the technical solutions of the present invention using the methods and techniques disclosed above, or modify them into equivalent embodiments with equivalent changes, without departing from the spirit and technical essence of the present invention. Therefore, any simple modifications, equivalent substitutions, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solutions of the present invention shall still fall within the protection scope of the technical solutions of the present invention.

Claims

1. A coated cutting tool with preferred orientation, characterized in that, The tool substrate (1) includes a wear-resistant coating (2) disposed on the tool substrate (1), the wear-resistant coating (2) comprising at least one layer of Al. x Ti 1-x N 1-y-z C y O z Coating (4), 0.65≤x≤0.98, 0<y<0.2, 0<z<0.18, the Al x Ti 1-x N 1-y-z C y O z The coating (4) has a preferred texture orientation relative to the {200} plane of the crystal, wherein the Al x Ti 1-x N 1-y-z C y O z The texture factor TC(200) of the coating (4) is ≥1.5; the full width at half maximum (FWHM) of the X-ray diffraction peak of the {200} plane of the crystal is <0.5°; the Al x Ti 1-x N 1-y-z C y O z The coating (4) is a periodic coating composed of alternating Al-rich layers with high Al content and Ti-rich layers with high Ti content, wherein both the Al-rich layers and the Ti-rich layers are nano-layered structures. TC(hkl) is defined as follows: ; in, I(hkl) = (hkl) the measured intensity of the reflected light; I0(hkl) = Standard intensity of reflection of (200) based on the standard powder diffraction data of the applied JCPDF card No. 00-46-1200; I(hkl) i =(hkl) i The intensity of the reflected light; I0(hkl) i =Based on the standard powder diffraction data (hkl) of the applied JCPDF card No. 00-46-1200 i Standard intensity of reflection; n = the number of reflections used in the calculation, here: n = 6; (hkl) i The (hkl) used i The reflective crystal planes are: (111), (200), (220), (311), (331) and (420).

2. The coated cutting tool with preferred orientation according to claim 1, characterized in that, Along the Al x Ti 1- x N 1-y-z C y O z In the growth direction of coating (4), the region on the Al element distribution curve that is higher than the average atomic fraction of Al in the coating is the period width d of the Al-rich layer. Al The region on the Al element distribution curve that is lower than the average atomic fraction of Al in the coating represents the period width d of the Ti-rich layer. Ti , satisfying d Al ≤150nm, d Ti ≤120nm.

3. The coated cutting tool with preferred orientation according to claim 2, characterized in that, d Al ≤100nm,d Ti ≤90nm。 4. The coated cutting tool with preferred orientation according to claim 3, characterized in that, d Al ≤50nm,d Ti ≤45nm。 5. The coated cutting tool with preferred orientation according to claim 2, characterized in that, Along the Al x Ti 1- x N 1-y-z C y O z The sum of the widths of each period of the Al-rich layer in the growth direction of coating (4) is d Al-total With the Al x Ti 1-x N 1-y-z C y O z The total thickness h of the coating (4) satisfies 0.5 < d Al-total / h<1.

6. The coated cutting tool with preferred orientation according to claim 1, characterized in that, The Al x Ti 1- x N 1-y-z C y O z The concentration of O element in the coating (4) varies periodically along the Al. x Ti 1-x N 1-y-z C y O z In the growth direction of coating (4), Al x Ti 1-x N 1-y-z C y O z The width between two adjacent peaks on the O element distribution curve in the coating is set as the period width d of the periodic concentration change of O element. O d O ≤200nm.

7. The coated cutting tool with preferred orientation according to any one of claims 1 to 6, characterized in that, The Al x Ti 1-x N 1-y-z C y O z The surface roughness Ra of the coating (4) is ≤0.25μm.

8. The coated cutting tool with preferred orientation according to any one of claims 1 to 6, characterized in that, The Al x Ti 1-x N 1-y-z C y O z The coating (4) has a face-centered cubic crystal structure of at least 85% by volume.

9. The coated cutting tool with preferred orientation according to claim 8, characterized in that, The Al x Ti 1- x N 1-y-z C y O z The coating (4) has a face-centered cubic crystal structure of at least 89% by volume.

10. The coated cutting tool with preferred orientation according to claim 9, characterized in that, The Al x Ti 1- x N 1-y-z C y O z The coating (4) has a face-centered cubic crystal structure of at least 93% by volume.

11. The coated cutting tool with preferred orientation according to any one of claims 1 to 6, characterized in that, The Al x Ti 1-x N 1-y-z C y O z The nanohardness of the coating (4) is ≥30GPa.

12. The coated cutting tool with preferred orientation according to any one of claims 1 to 6, characterized in that, The wear-resistant coating (2) also includes a coating disposed on the tool substrate (1) and the Al x Ti 1-x N 1-y-z C y O z A hard substrate layer (3) between the coatings (4), the thickness of the hard substrate layer (3) being 0.1 μm to 8 μm, the hard substrate layer (3) comprising one or a combination of CVD deposited TiN layer, TiCN layer and h-AlN layer.

13. The coated cutting tool with preferred orientation according to any one of claims 1 to 6, characterized in that, The wear-resistant coating (2) also includes a layer disposed on the Al x Ti 1-x N 1-y-z C y O z A hard surface layer (5) on top of the coating (4), the thickness of the hard surface layer (5) being >0.1 μm, the hard surface layer (5) comprising one or a combination of CVD deposited TiN layer, TiC layer, TiCN layer and h-AlN layer.

14. The coated cutting tool with preferred orientation according to any one of claims 1 to 6, characterized in that, The wear-resistant coating (2) has a total thickness of 2μm to 25μm.

Citation Information

Patent Citations

  • Surface-coated cutting tool having hard coating layer exerting excellent chipping resistance and wear resistance

    JP2019084671A

  • Hard-coated body and method for production thereof

    WO2007003648A1

  • Surface-coated cutting tool with rigid coating layers exhibiting excellent chipping resistance

    WO2016148056A1

  • Member covered with hard coating film and process for the production of the member

    CN101855035A

  • Coated cutting tool and preparation method thereof

    CN111893457A